HUBUNGAN MOTIVASI BELAJAR DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD PRESIDENT - Seprie (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to analyze the relationship between student motivation and parental attention toward the learning outcomes of Social Science (IPS) in fifth-grade students at SD President. The subjects of this study were fifth-grade students at SD President, while the research objects included student motivation, parental attention, and IPS learning outcomes. A correlational research approach was employed, with a sample size of 24 students selected from the entire fifth-grade population at SD President. Data were collected using scales to measure motivation, parental attention, and IPS learning outcomes. This study applied non-parametric statistics and was conducted on the entire population. The data analysis technique used was hypothesis testing through the product-moment correlation. The results indicate that at a 5% significance level, the correlation coefficient between motivation and parental attention toward learning outcomes was 0.565, which exceeds the critical value of 0.239. Therefore, it can be concluded that there is a significant positive relationship between student motivation, parental attention, and learning outcomes in IPS for fifth-grade students at SD President.